English Linguodidactic Discourse as Reflection of Situation in Modern Language Education in Japan (on Material of Terms of “Student” Category in English-Speaking Global and Local Linguodidactic Discourse of Japan) - I. G. Atroshchenko (Научный диалог, 2017)
The article is devoted to the interaction of global, Western-oriented and local Japanese English-speaking linguodidactic discourse in the educational space of Japan. The problem of the interaction of these discourses is considered by the author on the material of terms related to the basic categories of linguodidactics, namely the category of “Student.” It is expected that a thorough analysis of the terms in this category will determine the common spheres and differences between the interests of authors of discourses - native and non-native English speakers and, consequently, will identify the key provisions and challenges in modern language education in Japan. The relevance of the study and an appeal to the didactic discourse of Japan are determined by several factors. Firstly, the example of the Japanese educational environment helps to describe the interaction of didactic discourse and sociocultural context most fully. Secondly, study the English linguodidactic discourse of Japan is caused by the educational context of Russia and Japan, similar educational reforms and the contradictions that arise in the process of change. The novelty of the research is seen in the fact that in this work the discourse analysis was first carried out on the basis of the three-pronged analysis of the didactic term. This method of analysis allows to conduct interdisciplinary research, involving areas of discourse analysis, terminology and intercultural communication.